Association between family functioning and psychotic transition in ultra-high risk adolescents and young adults - Adrien, Vladimir; Liewig, Justine; Diot, Thomas; Ferreri, Florian; Mouchabac, Stephane; Dubertret, Caroline; Bourgin, Julie (Frontiers in Psychiatry, 2023)
Background Psychotic transition (PT) is a crucial stage in schizophrenia. The Comprehensive Assessment of At-Risk Mental States (CAARMS) scale can be used to identify individuals at ultra-high risk (UHR) for psychosis and to evaluate their risk of PT. Many environmental and genetic factors have been identified as contributing to the development and decompensation of schizophrenia. This study aimed to determine if the quality of family functioning is associated with PT risk in UHR individuals aged between 11 and 25 years after 1 year of follow-up. Methods From January to November 2017, 45 patients aged 12 to 25 consulting for psychiatric reasons were included. Twenty-six were classified as UHR of PT at the CAARMS. Family functioning was assessed by the Family Assessment Device—Global Functioning (FAD-GF). Thirty-seven of these patients (30% men, mean age 16 ± 2.5) were reassessed at 8–14 months of recruitment. Survival analysis was used to examine the impact of family functioning on PT risk. Results A total of 40% of UHR patients were classified as psychotic at reassessment. Survival analysis showed that better family functioning is a significant protective factor for PT in this population. Discussion This result suggests that the global family functioning has an impact at 1 year on the risk of PT in the population of adolescents and young adults who consult the hospital for psychiatric reasons. A family intervention may be effective in reducing PT risk in this population and should be considered as a potential therapeutic option.